Assessing the Combination of Jatropha Curcas Linnaeus and Cassia Fistula Oil Extracts as Bio-Fuel Source at Various Percentages - Egah, D. O.; Njoku, E. J.; Akinyemi, M. L.; Owoeye, T. F. (Journal of Informatics and Mathematical Sciences, 2017)
This project analysed the oil extract from two inedible seeds; Jatropha curcas Linnaeus and Cassia Fistula as a requirement for biofuel source. The quest for a clean source of energy has risen in recent times and this project attempts to proffer a solution to this challenge, whereby energy can be produced without the creation of an imbalance in the ecosystem. The purpose of this project is to examine the potentials of Jatropha curcas Linnaeus and Cassia Fistula for bioenergy production in Nigeria and reduce the reliance on fossil fuel. We compared the oils from both inedible seeds through series of test like UV-Vis spectrometer, viscosity, peroxide, saponification and acid value tests. From the analysis performed, it was observed that the combination of the two oils will be viable for biofuel production. The combination of the two oils at ratio \(9:1\) yielded a kinematic viscosity of 291.1nms \({}^{-2}\) and a dynamic viscosity of 249.18. While the individual kinematic and dynamic viscosities of Jatropha curcas Linnaeus was 190.01 nms\({}^{-2}\) and 160.56 respectively. It was also observed that the peroxide value of the mixture was 4.0mMol/kg and the saponification value was 160.2mgKOH\({}^{-1}\).